2019
DOI: 10.1097/md.0000000000016729
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic findings and outcome in caustic ingestion of acidic and alkaline agents in adults

Abstract: Caustic ingestion in adults is a rare but potentially life-threatening problem. It remains controversial whether endoscopic findings and mortality differ between acid and alkali ingestion. We compared ingestion of these agents and evaluated prediction parameters for survival and complications.Adult patients who presented with caustic ingestion were analyzed from 2005 to 2016. Mucosal injury was graded endoscopically by Zargar's score. Age, gender, intent of ingestion, caustic agents, comorbidities, management,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 29 publications
1
33
2
Order By: Relevance
“…In patients with stage IIB and III with damage from corrosive substance injury, a nasogastric tube for feeding should be placed within the first 24 h, and enteral fluids can be started within the first 48 h, especially if the patient can swallow his or her saliva [12] , [15] . Emergency surgery is indicated primarily on the clinical condition of the patient as compared to the radiological results.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with stage IIB and III with damage from corrosive substance injury, a nasogastric tube for feeding should be placed within the first 24 h, and enteral fluids can be started within the first 48 h, especially if the patient can swallow his or her saliva [12] , [15] . Emergency surgery is indicated primarily on the clinical condition of the patient as compared to the radiological results.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue injury caused by corrosive alkaline and acidic substances vary depending on the type, quantity, concentration, and contact time [ 9 ]. Acidic agent-driven corrosive esophagitis is rare; however, it can lead to a similar [ 10 ] or sometimes worse outcome [ 9 ] than that induced by alkaline agents.…”
Section: Discussionmentioning
confidence: 99%
“…After the correct identification of the features mentioned above, it is important to note that specific corrosive agents may cause other systemic effects such as hyponatremia, hypokalemia, and acidosis, especially with strong acids and alkalis, nevertheless, this is not always present. Moreover, it has been proven that the development of severe mucosal injury, renal failure, and mediastinitis have a worse prognosis [8]. For all the reasons explained above, the correct identification and prompt classification of the lesions using the endoscopic Zargar scale has great importance in these cases (Table 1).…”
Section: Table 1: Endoscopic Grading Of Caustic Injuries -Zargar Clas...mentioning
confidence: 99%
“…Hollenbach et al described that the patients over 65 years old and the ones who ingested alkali were more likely to develop severe lesions and had higher mortality. However, these data were obtained with a short sample, and studies with a greater cohort are suggested [8].…”
Section: Esophageal Stenosismentioning
confidence: 99%